Exploring diverse learning styles in elementary schools: A study on student preferences - Erviana, Vera Yuli; Fajaruddin, Syarief (International Journal of Education and Learning, 2023)
This study aimed to describe the learning style preferences of elementary school students in 5 districts in Yogyakarta. The population is 4th-grade and 5th-grade elementary school students in 5 districts in Yogyakarta. The sample was 992 students. Data was collected with a survey by questionnaire of learning style preferences. The results showed that the majority of elementary students have visual-kinesthetic (25.06%), the majority of students in Sleman district have kinesthetic (33.33%), the majority of students in Bantul district have visual-kinesthetic (31.93%), the majority of students in Gunungkidul district have the kinesthetic (27.45%), and the majority of students in Kulonprogo district have the visual-kinesthetic (29.36%). The elementary school students in Yogyakarta Province have more than one preference, a combination of two learning styles: visual-kinesthetic and auditory-kinesthetic. It can be concluded that the majority of students in Yogyakarta tend towards two learning styles, i.e., visual and kinesthetic.